Nano-graphene oxide composite for in vivo imaging - Jang, Sung-Chan (Int J Nanomedicine, 2018)
INTRODUCTION: Positron emission tomography (PET) tracers has the potential to revolutionize cancer imaging and diagnosis. PET tracers offer non-invasive quantitative imaging in biotechnology and biomedical applications, but it requires radioisotopes as radioactive imaging tracers or radiopharmaceuticals. METHOD: This paper reports the synthesis of (18)F-nGO-PEG by covalently functionalizing PEG with nano-graphene oxide, and its excellent stability in physiological solutions. Using a green synthesis route, nGO is then functionalized with a biocompatible PEG polymer to acquire high stability in PBS and DMEM. RESULTS AND DISCUSSION: The radiochemical safety of (18)F-nGO-PEG was measured by a reactive oxygen species and cell viability test. The biodistribution of (18)F-nGO-PEG could be observed easily by PET, which suggested the significantly high sensitivity tumor uptake of (18)F-nGO-PEG and in a tumor bearing CT-26 mouse compared to the control. (18)F-nGO-PEG was applied successfully as an efficient radiotracer or drug agent in vivo using PET imaging. This article is expected to assist many researchers in the fabrication of (18)F-labeled graphene-based bio-conjugates with high reproducibility for applications in the biomedicine field.